Comparison of Positive Politeness Strategies by Ellen to Interact with Her Guests of Age Groups - Yuliana Maula; Januarius Mujiyanto; Henrikus Joko Yulianto (English Education Journal, 2023)
Politeness cannot be achieved directly when people are born because of genetic factors or special characteristics given by God. It needs to be learned, and they should consider whom they speak to establish a good relationship between the speaker (S) and hearer (H) in the social interaction. This study aims to explain the similarities and differences between the use of positive politeness strategies by Ellen in her interaction with adult and young guests. The transcript of Ellen’s talk show becomes the primary source of this study where the data were analyzed by using Brown and Levinson’s theory. This study was descriptive qualitative research with a pragmatic approach. Based on the data analysis, Ellen applied noticing, exaggerating, and intensifying interest to H, using in-group identity markers, seeking agreement, asserting common ground, being optimistic, including S and H in the activity, and giving gifts in her communication with adult and young guests. The strategy of using in-group identity markers is frequently used in Ellen’s interaction with a percentage of 27,8%. In addition, in Ellen’s interaction with the young guests, the noticing strategy is the most dominant strategy with a percentage of 25%. The strategies of avoiding disagreement, joking, promising, and giving reasons were only applied in her interaction with the adult guests. Therefore, Ellen’s decision to use these positive politeness strategies can save the hearers’ positive face and maintain the relationship among them. As a result, this study contributes to English language teaching in class interaction, especially in fulfilling the students’ positive face.